High-concentrated platelet-rich plasma (PRP) versus placebo in osteoarthritis in the thumb base: study protocol for an assessor-blinded randomized controlled trial - Johanna von Kieseritzky; Maria Wilcke (Trials, 2024)
Abstract Background Osteoarthritis in the thumb base (trapeziometacarpal joint, CMC-1 joint) is prevalent, particularly among middle-aged and elderly women, causing significant disability. Conservative treatments, including steroid injections, have been questioned for their efficacy, prompting exploration into alternative therapies such as platelet-rich plasma (PRP) injections. This randomized, double-blinded, controlled trial aims to evaluate the effectiveness of high-concentration PRP (platelet-rich plasma) injection compared to saline (placebo) in reducing pain and disability in patients with thumb base osteoarthritis. Methods Patients meeting inclusion criteria will be randomized and blinded, with injections administered under sterile conditions and radiological guidance. With a planned sample size of 90 patients recruited from the Department of Hand Surgery at Södersjukhuset, Stockholm, the study will assess pain relief and functional improvement at 3, 6, and 12 months post-injection. The primary outcome measure is pain on load (numerical rating scale) at 6 months, with secondary outcomes including patient-reported outcomes, key pinch, grip strength, abduction of the thumb, and time to intervention within 1 year. Statistical analyses will employ non-parametric tests, chi-square tests, and generalized estimating equations to compare outcomes between the PRP and placebo groups. Discussion The study aims to provide evidence regarding the efficacy of high-concentration PRP injections for thumb base osteoarthritis. If PRP proves superior to saline in reducing pain and improving function, it could offer a promising alternative treatment. Conversely, if PRP does not demonstrate significant benefits over placebo, its use for this condition is not justified. This study seeks to address the current gap in evidence regarding the efficacy of PRP injections for thumb base osteoarthritis. Trial registration The study has been approved by the Swedish Ethical Review Authority (2023–06860-01 and 2024–01238-02) and is registered on ClinicalTrials.gov (NCT06193499) 2024–01-04.